Relationships Between Mathematical Visuality, Mathematical Performance, Word Problem Solving Ability and Attitude Toward Learning of Mathematics Among Lower Secondary School Students - Yip, Siew Ha (2011)
The purpose of this study was to investigate students’ mathematical visuality when solving mathematical problems. Form Two students (N=333) from a Chinese Independent School and a National School participated in this study. The lower secondary mathematics curriculums for two types of schools were studied. Students were assessed on measures of mathematical visuality when solving mathematical word problem, mathematical performance based on school assessment, performance when solving word problem and attitude towards learning of mathematics. The mathematical visuality measures to what extent a student prefer to use visual or analytic method when solving mathematical word problems. The mathematical visuality was measured by an instrument adopted from Suwarsono’s Mathematical Processing Instrument. School based mathematical performance was measured by students’ mathematical achievement based on first semester assessment in school. The performance when solving word problem was measured by Mathematical Processing Test whilst attitude towards learning of mathematics was measured by a set of questionnaire. The descriptive statistic was employed to analyze and describe the variables involved in this study whilst the Pearson Product Moment Coefficient was used to measure the relationship between the variables. Results indicated that students from both schools used significantly more analytic methods than visual methods when solving mathematical word problem. Mathematical visuality was negatively correlated with the school based mathematical performance (r(160)=- 205,p < 0.01)for Chinese Independent School students. Mathematical visuality was negatively correlated with performance when solving word problem (r(160)=- 289,p < 0.01) for Chinese Independent School students. Mathematical visuality was also negatively correlated with attitude towards learning of mathematics(r(160)=- 228,p < 0.01) for Chinese Independent School students. The negative correlation among the variables shows that the lower the mathematical visuality, the students tend to have higher school based mathematical performance, performance when solving word problem and attitude towards learning of mathematics. However, mathematical visuality was not significantly correlated with school based mathematical performance, performance when solving word problem and attitude towards learning of mathematics for National School students. It was found that the attitude towards learning of mathematics was significantly correlated with school based mathematical performance for students from Chinese Independent School and National School.